A Cross-Species Transmission of a Camel-Derived Genotype 8 Hepatitis E Virus to Rabbits - Wenjing Zhang (MDPI AG, 2021)
Novel genotypes of hepatitis E virus (HEV), i.e., HEV-5, HEV-7, and HEV-8, have been identified in wild boar, dromedary camels, and Bactrian camels, respectively, and they transmit to cynomolgus monkeys in a trans-species manner, raising the potential for zoonotic infection. Rabbits are the natural reservoir for rabbit HEV, but they are also susceptible to HEV-3 and HEV-4. It has been unknown whether rabbits are susceptible to HEV-5, HEV-7, and HEV-8. To investigate the infectivity of novel HEVs in rabbits and to assess whether rabbits are appropriate animal models for these HEVs, we inoculated Japanese white rabbits with HEV-5, HEV-7, and HEV-8, respectively. We observed that viral RNA was present in the fecal specimens of the HEV-8-inoculated rabbits and anti-HEV IgG antibodies were present in its sera, although anti-HEV IgM was undetectable and no significant elevation of ALT was observed. These results indicated that HEV-8 crossed species and infected the rabbits. No evidence for replication was observed in HEV-5 and HEV-7, suggesting that rabbits are not susceptible to these genotypes. The antibodies elicited in the HEV-8-infected rabbits did not protect them from the rabbit HEV challenge, suggesting that the antigenicity differs between HEV-8 and rabbit HEV. Antigenic analyses demonstrated that anti-HEV-8 antibodies reacted more strongly with homologous HEV-8 virus-like particles (VLPs) compared to heterologous rabbit HEV VLPs, but anti-rabbit HEV antibody had similar reactivity to the VLPs of rabbit HEV and HEV-8, suggesting that HEV-8 lacks some epitope(s) that exist in rabbit HEV and induced the neutralizing antibodies against rabbit HEV.